2013
DOI: 10.3389/fpsyg.2013.00459
|View full text |Cite
|
Sign up to set email alerts
|

Development of numerical processing in children with typical and dyscalculic arithmetic skills—a longitudinal study

Abstract: Numerical processing has been demonstrated to be closely associated with arithmetic skills, however, our knowledge on the development of the relevant cognitive mechanisms is limited. The present longitudinal study investigated the developmental trajectories of numerical processing in 42 children with age-adequate arithmetic development and 41 children with dyscalculia over a 2-year period from beginning of Grade 2, when children were 7; 6 years old, to beginning of Grade 4. A battery of numerical processing ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
78
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 56 publications
(108 reference statements)
12
78
1
6
Order By: Relevance
“…First, with respect to number access, our results were in agreement with those reported by De Smedt and Gilmore (2011), Landerl andKölle (2009), andNoël (2007), who found that children with MLD had difficulty comparing Arabic numbers. Indeed, children with MLD in the present study were less successful and slower than TD children not only in Arabic but also in spoken number comparison and judgment, pointing to a number comprehension deficit in both symbolic codes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…First, with respect to number access, our results were in agreement with those reported by De Smedt and Gilmore (2011), Landerl andKölle (2009), andNoël (2007), who found that children with MLD had difficulty comparing Arabic numbers. Indeed, children with MLD in the present study were less successful and slower than TD children not only in Arabic but also in spoken number comparison and judgment, pointing to a number comprehension deficit in both symbolic codes.…”
Section: Discussionsupporting
confidence: 93%
“…This is also the case in various studies on MLD in which children presented with mathematical difficulties, along with learning, cognitive and/or linguistic impairment (e.g., Ashkenazi, Mark-Zigdon, & Henik, 2013;Andersson & Östergren, 2012;Landerl, 2013). Thus, our results provide support to the hypothesis that MLD is caused by multiple numerical and general cognitive deficits (Geary, 1993(Geary, , 2010.…”
Section: Discussionsupporting
confidence: 87%
“…En definitiva, los resultados del presente estudio sugieren que competencias numéricas básicas como la comparación de magnitudes numéricas (especialmente las simbólicas) y la enumeración pueden tener un papel relevante en la adquisición temprana de la aritmética, y de esta forma constituir marcadores nucleares de la competencia aritmética y por lo tanto tener un valor diagnóstico desde el punto de vista de la prevención y la detección de niños con riesgo de padecer dificultades específicas en el aprendizaje de la aritmética. De hecho, algunos estudios han demostrado que los discalcúlicos presentan déficits específicos tanto en tareas de comparación de magnitudes numéricas simbólicas (e.g., De Smedt&Gilmore, 2011), como en tareas de enumeración, especialmente en el rango de subitizing (e.g., Landerl, 2013).…”
Section: Discussionunclassified
“…Dot counting: In dot enumeration tasks, which are aimed at measuring the numerical learning capacity, subjects are required to rapidly and accurately determine the number of dots presented, usually less than 10 dots (15). Human brain can determine one to three or four dots at a glance without counting (12).…”
Section: Introductionmentioning
confidence: 99%